(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدّراسة إلى التَّعرف على العلاقة بين إدارة المعرفة وتحديد الاحتياجات التّدريبيّة في جامعة تشرين؛ من خلال تحديد دور إدارة المعرفة في عمليّة تحديد الاحتياجات التَّدريبيّة، وقد اعتمد الباحث على كل من المقاربة الاستنباطيَّة كمنهج عام للبحث، والمنهج الوصفي، وقام بتوزيع استبانة على (303) من العاملين في الإدارة المركزيّة في جامعة تشرين، تمَّ استرداد (274) استبانة، كان صالحاً منها للاستخدام (264) استبانة، ومن ثمَّ أجريت دراسة ميدانيّة بغرض بيان هذه العلاقة، حيث قام الباحث باستخدام معامل ارتباط بيرسون (Pearson)، وكذلك معامل التّحديد (R Square). توصّل الباحث من خلال الدّراسة إلى وجود ممارسة ولو كانت مقبولة إلى حدٍّ ما لإدارة المعرفة في جامعة تشرين، بالإضافة إلى وجود ضعف من جانب الإدارة العليا في الجامعة محل البحث في دعم عمليّة تحديد الاحتياجات التَّدريبيّة. وقد خلصت الدّراسة إلى وجود علاقة طرديّة معنويّة بين إدارة المعرفة وعمليّة تحديد الاحتياجات التَّدريبيّة؛ وبالتَّالي وجود دور لإدارة المعرفة في عمليّة تحديد الاحتياجات التَّدريبيّة في جامعة تشرين؛ كما توصّلت هذه الدّراسة إلى مجموعة من التّوصيات والمقترحات، والَّتي من شأنها أن تسهم بشكلٍ إيجابي بتحسين دور إدارة المعرفة في عمليّة تحديد الاحتياجات التَّدريبيّة. The aim of this study is to identify the relationship between Knowledge Management and Identification of Training Needs at Tishreen University by defining the role of Knowledge Management in the Process of Identifying Training Needs. The researcher relied on Both, the Deductive Approach as a general method, and the Descriptive Approach. He distributed a questionnaire to (303) of Employees in the Central Administration at Tishreen University, retrieving (274) Questionnaires, which were valid for use (264) questionnaire, and then conducted a field study for the purpose of this relationship, where the researcher used Pearson Correlation Coefficient, as well as the Coefficient of Selection. The researcher found through the study, that there is a fairly acceptable practice of Knowledge Management at Tishreen University, in addition to the weakness of the Senior Management of the University in the research in Support of the Process of Identifying Training Needs. The study concluded that there is a significant relationship between Knowledge Management and the Process of Identifying Training Needs. Therefore, there is a Role of Knowledge Management in the Process of Identifying Training Needs at Tishreen University. This study also reached a set of recommendations and proposals that would positively contribute to improving the role of Knowledge Management in the Process of Identifying Training Needs.